Infección por virus HTLV-1/2 confirmada por serología y detección de provirus en pacientes ecuatorianos de paraparesis espástica tropical - Carmen Mosquera (Asociación Colombiana de Infectología, 2020)
Background: Infection with the Human T-cell lymphotropic virus (HTLV) type 1 and 2 is endemic in South America. There are only a few clinical reports of this retrovirus in patients in Ecuador, without employing virus-isolation methods or viral DNA detection. The infection is usually neglected in health care settings and by public health authorities and no country wide prevalence data are available. Objectives: This study aims to detect the HTLV-1/2 infection in symptomatic individuals for tropical spastic paraparesis (TSP) using for the first time in Ecuador both immunological and molecular biology methodologies. Study Design: Blood samples of 9 symptomatic individuals with myelopathy were analyzed for the detection of the HTLV-1/2 virus with three methods: ELISA, an indirect immunofluorescence (IF) assay and a nested-PCR. Results: Five out of 9 (55.5%) myelopathy patients were positive for ELISA, IF and nested- HTLV-1/2 PCR. Conclusion. The high prevalence of HTLV-1/2 infection among myelopathy patients shows the endemicity of this retrovirus in Ecuador, the association of HTLV-1/2 infection with TSP and the need of the implementation of control and prevention interventions to overcome the further dissemination of this neglected infectious disease.